Neuro‐Ophthalmological Findings in Early Fatal Familial Insomnia. Issue 4 (11th January 2021) - Mastrangelo, Vincenzo; Merli, Elena; Rucker, Janet C.; Eggenberger, Eric R.; Zee, David S.; Cortelli, Pietro
Abstract : Fatal familial insomnia (FFI) is a rare inherited prion disease characterized by sleep, autonomic, and motor disturbances. Neuro‐ophthalmological abnormalities have been reported at the onset of disease, although not further characterized. We analyzed video recordings of eye movements of 6 patients with FFI from 3 unrelated kindreds, seen within 6 months from the onset of illness. Excessive saccadic intrusions were the most prominent findings. In patients with severe insomnia, striking saccadic intrusions are an early diagnostic clue for FFI. The fact that the thalamus is the first structure affected in FFI also suggests its role in the control of steady fixation. ANN NEUROL 2021;89:823–827